Knockdown of Dcr1 and Dcr2 limits the lethal effect of C‐factor in Chilo suppressalis. Issue 1 (13th February 2023) - Yao, Zhuotian; Jin, Huihui; Li, Changyan; Ma, Weihua; Zhang, Wei; Lin, Yongjun
Abstract: Dicer is a highly conserved ribonuclease in evolution. It belongs to the RNase III family and can specifically recognize and cleave double‐stranded RNA (dsRNA). In this study, the genome and transcriptome of Chilo suppressalis were analyzed, and it was found that there were two members in the Dicer family, named Dcr1 and Dcr2 . The dsRNAs of Dcr1 and Dcr2 genes were synthesized and fed to C. suppressalis larvae. The C‐factor of C. suppressalis was selected as the marker gene. The results showed that both Dcr1 and Dcr2 genes were significantly knocked down. The larval mortality was significantly reduced by 43.50% ( p < 0.05) after feeding on ds C‐factor and ds Dcr1 . The transcription levels of C‐factor genes were significantly increased by 33.95% ( p < 0.05) and 32.94% ( p < 0.05) when the larvae fed with ds Dcr2 + ds C‐factor for 72 h and 96 h, respectively. Furthermore, the mortality was significantly decreased by 79% ( p < 0.05) after feeding ds C‐factor and ds Dcr2 . These findings imply that Dcr1 can decrease the lethal effect of C‐factor gene but cannot affect its RNAi efficiency and Dcr2 can decrease the lethal effect of C‐factor gene by inhibiting RNAi efficiency. Abstract : The genome of Chilo suppressalis were analyzed, and it was found that there were two members in the Dicer family, named Dcr1 and Dcr2 . The C‐factor of C. suppressalis was selected as the marker gene. Both Dcr1 and Dcr2 genes were significantly knocked down. Dcr1 can decrease the lethal effect of C‐factor gene but cannot affect its RNAi efficiency and Dcr2 can decrease the lethal effect of C‐factor gene by inhibiting RNAi efficiency. Highlights: The genome and transcriptome of Chilo suppressalis were analyzed, and it was found that there were two members in the Dicer family, named Dcr1 and Dcr2 . Dcr1 can decrease the lethal effect of C‐factor gene but cannot affect its RNAi efficiency and Dcr2 can decrease the lethal effect of C‐factor gene by inhibiting RNAi efficiency.